1992
DOI: 10.1093/ajcn/56.3.526
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin requirements and exercise adaptation in older women

Abstract: The effects of exercise training on riboflavin requirements and of riboflavin intake on endurance were examined in 14 women, 50-67 y of age, who participated in a 10-wk, two-period crossover exercise study at two riboflavin intakes, 0.15 micrograms/kJ (0.6 micrograms/kcal) and 0.22 micrograms/kJ (0.9 micrograms/kcal). Subjects exercised 20-25 min/d, 6 d/wk, for 4-wk periods on a cycle ergometer at 75-85% of their maximal heart rate. Riboflavin status was assessed by measuring the erythrocyte glutathione reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The impact of vitamin status on functional capacities has been described in some studies. In other studies no effect of marginal vitamin depletion or of vitamin supplementation was found on physical performance of elderly women [54] or young subjects (23 years of age) [55]. Although data from 30 human studies were summarized in a workshop discussing this issue, no clear set of conclusions was drawn regarding the effect of micronutrient intake on physical work capacity [9].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of vitamin status on functional capacities has been described in some studies. In other studies no effect of marginal vitamin depletion or of vitamin supplementation was found on physical performance of elderly women [54] or young subjects (23 years of age) [55]. Although data from 30 human studies were summarized in a workshop discussing this issue, no clear set of conclusions was drawn regarding the effect of micronutrient intake on physical work capacity [9].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, 1.6 mg of riboflavin/1000 kcal (2 mg/day) was required to maintain good riboflavin status when the women were dieting for weight loss and exercising. In a similar study, active older women (2.5 h exercise/week) consuming a weight maintenance diet (1800 to 2000 kcal/day) required 1.8 mg/day of riboflavin to maintain good status (Winters et al 1992). Thus, exercise, dieting, and dieting plus exercise increase the need for riboflavin above the 1998 RDA for women (Belko et al 1983(Belko et al , 1984(Belko et al , 1985Winters et al 1992;Food and Nutrition Board 1998).…”
Section: Dietary Intake and Status Of Riboflavin In Active Adultsmentioning
confidence: 99%
“…However, some studies suggest that female athletes might be at risk for poor riboflavin status due to increased nutrient needs. Metabolic studies have examined the effect of exercise, dieting, or dieting plus exercise on riboflavin requirements in women (Belko et al 1983(Belko et al , 1984(Belko et al , 1985Winters et al 1992); overall results suggest that riboflavin needs are higher in females engaging in exercise for fitness compared to sedentary controls. Belko et al (1983Belko et al ( , 1984Belko et al ( , 1985 completed a series of metabolic studies examining the riboflavin status of active young women.…”
Section: Dietary Intake and Status Of Riboflavin In Active Adultsmentioning
confidence: 99%
“…Deterioration of riboflavin status can occur due to extensive physical activity as flavin enzymes are involved in cellular respiration and energy production. Several non-dietary factors may also contribute to high prevalence of subclinical (biochemical) riboflavin deficiency 47 . Pyridoxine (vitamin B 6 ) status was determined using an estimation of erythrocyte Aspartate aminotransferase and its activation by pyridoxal 5' phosphate in vitro.…”
Section: Table5mentioning
confidence: 99%